ANÁLISIS FORMAL Y FUNCIONAL DE LA MANCHETA Y EL BLOQUE DE CABECERA EN LA PRENSA DIGITAL DE INFORMACIÓN GENERAL EN ESPAÑA - Dr. Manuel MONTES VOZMEDIANO,Dr. Carlos JIMÉNEZ NARROS (Fonseca, Journal of Communication, 2023)
This work analyzes the formal aspect of the headboards, as well as the visual communication and the functional contribution of the header blocks in the Spanish online press of general information, with the purpose of knowing the communicative guidelines and the practical support that they contribute to the media user. In the research, the methodology of content analysis is used and the recording of the data is carried out by means of a self-created analysis instrument, mostly made up of manifest variables.